Rekonstruksi Regulasi terhadap KPK dalam Pemberantasan Kasus Tindak Pidana Korupsi di Indonesia - Dina Aprilia Iswara (Jurnal Hukum Lex Generalis, 2020)
Corruption is a particular crime that provides losses, especially to the country's finances. Corruption itself can occur in various sectors both public and private. Due to the consequences of corruption that provide large scale, there is an urgency for the return of state finances from the results of corruption. In the public sector, it can be done to counter corruption by doing a reverse proof or what is referred to as Omkering van het Bewijslast or Reversal Burden of Proof because of the nature of corruption itself that is systematic and difficult to sniff by law enforcement. While in the private sector, one of the things that can be done is to utilize the institution Stolen Asset Recovery (StAR) which is the result of cooperation between the World Bank and UNODC with developing countries to prevent the laundering of corruption, with Mutual Legal Assistance as its upstream. In addition, private in the domestic sector can take advantage of the role of whistleblowers who will report on alleged criminal acts of corruption in the private sector. In general, to suppress or minimize the possibility of criminal acts of corruption can be used preventive-moralistic measures such as preparing a government order based on Good Governance. While further strengthened by repressive-proactive measures by optimizing the use of the Corruption Act and the Money Laundering Act as downstream from handling corruption in Indonesia.